Experimental investigation on energy absorption of auxetic foamfilled thin-walled square tubes under quasi-static loading - Mohsenizadeh, Saeid (2015)
Auxetic materials are modern class of materials that have recently been gaining popularity within the research community due to their enhanced mechanical properties. Unlike conventional materials, they exhibit a negative Poisson's ratio when subjected to a uniaxial loading. This present research experimentally investigates the crush response and energy absorption performances of auxetic foam-filled square tubes under axial loading. For comparison, the crush response and energy absorption of empty and conventional foam-filled squares tubes have also been examined with respect to deformation modes and force displacement curve. Standard compression tests were conducted on a series number of thin-walled tube samples. An additional compression test on conventional and auxetic foam has also been conducted to observe the behavior of foam itself. It is evident that the auxetic foam-filled square tubes are superior to empty and conventional foam-filled square tubes in terms of energy absorption capacity. It shows that such tube is preferable as an impact energy absorber due to their ability to withstand axial loads effectively. Furthermore, it is found that the load capacity increases as the crush length increases. The primary outcome of this study is design information for the use of auxetic foam-filled square tubes as energy absorbers where impact loading is expected particularly in crashworthiness applications.